Extracorporeal shock wave therapy for the treatment of chronic pelvic pain syndrome - Skaudickas Darijus; Telksnys Titas; Veikutis Vincentas; Aniulis Povilas; Jievaltas Mindaugas (Open Medicine, 2020)
Prostatitis is the most commonly diagnosed disease in men younger than 50 years and accounts for about 8% of all urologists’ consultations.